Atomic layer deposition of SnO2 enables fast-dynamics in electrochromic vanadium oxide/polyaniline films - Yixin Song; Lihao Zhou; Xianghong Liu; Jun Zhang (Next Materials)
Heterostructure materials hold great promise for electrochromism, but the complexity in coupling the optical and electronic properties of multiple materials remains a challenge. Herein, SnO2 film with excellent transparency and electronic properties is deposited on electro-deposited inorganic-organic vanadium oxide-polyaniline composite films by atomic layer deopisiton (ALD). As a result, the heterostructure strategy stimulated the reaction dynamics, significantly reducing the response time (from 30 s to 5 s). In addition, the thickness of the SnO2 films is found to have a crucial influecne on the electrochromic performance of heterostructure electrodes. Our work highlights the potential of semiconductor films in improving the electrochoromic materials.